(untitled) (Studia Prawnicze / The Legal Studies, 2012)
Nauczanie religii należy bezsprzecznie do najbardziej wrażliwej, a co za tym idzie i spornej kwestii w bilateralnych stosunkach państwa z Kościołem. Uwolnienie szkoły spod kurateli Kościoła, tak jak to miało miejsce w bardzo stanowczej i jednoznacznej formie chociażby we Francji, było wszak niemalże synonimem nowej, całkowicie zmienionej koncepcji ładu światopoglądowego; fragmentem znacznie szerszej emancypacji państwa, która w swoich skutkach zakładała wprowadzenie wyraźnej linii demarkacyjnej między sferą sacruma profanum. Jednocześnie jednak, mimo ustanawiania – w bardzo zresztą rozmaitych wersjach aplikacyjnych – systemu rozdziału między państwem a Kościołem, sprawa nauczania religii czy w ogóle wychowania znajdowała się w przysłowiowej orbicie wpływów obu podmiotów, będąc wręcz podręcznikowym przykładem materii mieszanej (res mixtae), a zatem takiej, z której – z oczywistych powodów – nie może zrezygnować ani państwo, ani Kościół. Kształtowanie formacji intelektualnej młodego człowieka było wszak i nadal pozostaje sprawą w jednakowym stopniu państwa i Kościoła. The article presents the position of the Polish Constitutional Tribunal with regard to denominational matters. An example is the judgment relating to the problem of counting the assessment of the religion of the students’ grade point average. This case is a good illustration of a peculiar spirit of the polish constitutional court or his philosophy on the religious and ideological matters. This spirit, in many cases is penetrated by the position of preferring a specific religion and specific religious association. As a result, it is difficult to talk about the neutral position of the Constitutional Tribunal. For the described case, the Court clearly took a position in support for specific legal solutions, while – it seems – there was no pattern of constitutional assessment of the whole matter. The Constitution of 1997 is not of a standard to evaluate whether the assessment of the religion taught in public school should be or should not be included in the students’ grade point average. Therefore, the Constitutional Tribunal should consider that any legislative solution is in line with the Constitution. If only given to other constitutional principles, such as a secular state and its neutrality, the court’s line of argument should go the other way. Meanwhile, the Constitutional Tribunal found that not only the solution adopted is consistent with the Constitution, but virtually every other solution would be unconstitutional. The Tribunal holds that, if consistent with the Constitution are the lessons of religion and if consistent with the Constitution is to include evaluation of religion on school certificates, then the counting of this assessment to the average grade is in accordance with the Constitution. It seems that the present case shows a well-partisan position of the polish Constitutional Tribunal. In this case, the Tribunal as a starting point for the case considered the constitutionality of teaching religion in school. Meanwhile, the case is undeniable and inevitable. The Constitution expressly provides, after all, that religion can be taught in public school. The court therefore made the subject of their deliberations something that is obvious. For the Court, it was necessary, however, because it relied on a simple logic, such as teaching religion in schools is in line with the constitution and the general effects of this result is also consistent with the Constitution. Another line of reasoning of the Constitutional Tribunal in this case must be considered as lack of impartiality of the court. That is not its only case when the court takes the position of one-sided, which conflicts with the constitutional principle of state neutrality and independence of church and state.